An Analysis of Trends and Themes in Research Articles on Canadian Student Services - Clarke, Kathleen; Arnold, Christine Helen (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2021)
Student services professionals have emerged as significant supportive collaborators in the construction ofvenvironments that encourage student success within Canadian post-secondary education (Hardy-Cox & Strange, 2010). In Canada, literature pertaining to student services is evolving and research from other contexts is therefore often used to inform student affairs practices in this context. Yet, without a comprehensive understanding of research that is focused on Canadian student services specifically, those working in post-secondary education are left with a scope of understanding that may not always apply to the unique contexts in which they work. The purpose of this research study is to begin mapping the landscape of re-search on Canadian student services. We review articles pertaining to student success, the student experience, and student services, that have been published in national (Canadian Journal of Higher Education) and international (Journal of College Student Development; Journal of College Student Retention: Research, Theory and Practice; Journal of College Student Psychotherapy; Journal of Student Affairs Research and Practice; and Student Success) student services and post-secondary education journals. This scoping review documents Canadian academic research published within the student services field and describes contributing authors and their affiliations, graduate student and post-doctoral fellow involvement, provincial and territorial research clusters, research movements over the decades, institutional research contexts, and research participants’ level of education and communities/populations, as well as contextual trends and themes.